Aligning Intentions with Community: Graduate Students Reflect on Collaborative Methodologies with Indigenous Research Partners - Kristine Wray; Akarath Soukhaphon; Brenda Parlee; Amabel D’Souza; Carolina Freitas; Iria Heredia; Chelsea Martin; Carrie Oloriz; Tracey Proverbs; Neal Spicer (Sustainability, 2020)
Collaborative and community-based research (CCBR) is well defined and discussed in the literature; however, there are few discussions about graduate students doing CCBR with Indigenous communities. This project report features insights from nine graduate students attending six universities in Canada, the United States, and Brazil. These students are a part of a multi-year research partnership grant involving fishing communities from three major watersheds, the Mackenzie River Basin, the Amazon River Basin, and the lower Mekong River Basin. Each student engaged in collaborative research around the themes of Indigenous fishing livelihoods and the role of local and traditional knowledge in river basin governance. This project report presents reflections of graduate students on developing relationships and enacting CCBR during the following three stages of research with Indigenous communities: research project design, research project implementation, and post-project engagement. Best practices have been developed from graduate student reflections on issues, challenges, and needs of graduate students doing CCBR. The findings suggest that a diversity of factors contribute to effective CCBR. This includes the needs and interests of the community partner, the quality of supervisor support, the skillset of the student, their disciplinary background, and their capacity to work in complex sociopolitical contexts.